Clinical Characteristics of Juvenile Myasthenia Gravis in Southern China - Huang, Xin; Li, Yingkai; Feng, Huiyu; Chen, Pei; Liu, Weibin (Frontiers in Neurology, 2018)
Objectives: To describe the clinical profile, clinical outcomes and factors that may affect the outcome of juvenile myasthenia gravis (JMG) patients in southern China. Methods: We reviewed information relating to JMG patients treated and evaluated at the First Affiliated Hospital, Sun Yat-Sen University, between 1998 and 2015. The study involved 327 JMG patients who had been followed up for ≥1 year. Results: Overall, 77.4% patients showed initial symptoms in the prepubertal period (<12 years). 306 patients showed only ocular symptoms at onset. By the final follow-up, 61 ocular myasthenia gravis (OMG) patients (61/306, 19.9%) had developed generalized myasthenia gravis (GMG). Anti-acetylcholine receptor antibody (AChR-Ab) titer was an independent risk factor for generalization. Eleven patients (3.4%) experienced spontaneous remission, but four relapsed. Low-dose oral prednisone (0.25mg/kg) was administered when symptoms did not significantly improve after pyridostigmine treatment. Immunosuppressants were administered when prednisone was unsatisfactory. Optimal outcome was achieved in 59.6% of patients. Specifically, 60 patients (18.3%) attained complete stable remission (CSR), 12 (3.7%) attained pharmaceutical remission(PR) and 123 (37.6%) attained minimal manifestation(MM). In total, 53 OMG patients (21.5%) attained CSR, a significantly higher proportion than among the GMG patients (8.6%, P=0.009). Moreover, 67.2% of patients with duration <2 years showed significant clinical improvement compared with 46.3% of those with duration >2 years (P<0.001). Thymectomy did not exhibit definite efficacy for JMG patients. Conclusion: There was a low frequency of cases positive for AChR-Ab in the Chinese population. AChR-Ab titer was revealed as an independent risk factor for generalization. Low doses of prednisone could treat JMG effectively with few side effects.